2003
DOI: 10.1093/annonc/mdg028
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in women with previous breast cancer

Abstract: This analysis confirms the existence of a modest excess in several neoplasms occurring after breast cancer. The substantial excess of STS confirms the strong association between irradiation and STS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
83
1
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 10 publications
3
83
1
4
Order By: Relevance
“…Our observation of increasing risks by latency and lack of reverse associations supported that the excesses of cancers of the esophagus, lung, stomach and soft tissue may at least partly be a consequence of treatment for breast cancer. With the exception of esophageal cancer, these types of cancer have also been found in excess in other studies 2,4,6,7,[10][11][12][13]15 and risks of esophageal cancer, lung cancer and soft tissue sarcoma have been found to be higher, in particular during long-term follow-up, among patients treated with radiotherapy compared to those not treated in some studies. 12,[19][20][21][22] The risk estimates for these cancers among those followed for 10 or more years tended to be lower after 1975.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our observation of increasing risks by latency and lack of reverse associations supported that the excesses of cancers of the esophagus, lung, stomach and soft tissue may at least partly be a consequence of treatment for breast cancer. With the exception of esophageal cancer, these types of cancer have also been found in excess in other studies 2,4,6,7,[10][11][12][13]15 and risks of esophageal cancer, lung cancer and soft tissue sarcoma have been found to be higher, in particular during long-term follow-up, among patients treated with radiotherapy compared to those not treated in some studies. 12,[19][20][21][22] The risk estimates for these cancers among those followed for 10 or more years tended to be lower after 1975.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies reported an overall excess of 20-30% for second primary cancer not including contralateral breast cancer. Excesses of various cancer sites have been shown, with the most consistent findings for cancer of the endometrium, 2,4,6,7,[11][12][13]15 ovary, 3,4,6,7,9,[11][12][13] thyroid gland 3,7,[10][11][12] and lung, 4,7,[11][12][13] as well as soft tissue sarcomas 2,4,6,12,13 and leukaemia. 4,6,11,13,14 Excesses of melanoma, 6,7,12,13 stomach 4,10,15 and colon cancer [10][11][12] have also been reported.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…[1][2][3] Some articles have described an increased risk of primary lung cancers in association with radiation therapy following mastectomy. 4,5 Furthermore, the long latent period before identification of metastasis makes a differential diagnosis challenging.…”
mentioning
confidence: 99%
“…A number of non-cutaneous carcinomas have been shown to have associations with melanoma. Among women with a history of previous breast cancer, there is a standardized incidence ratio of 1.4 signifying an increased risk for cutaneous malignant melanoma among a Swiss Cancer Registry including 9,729 breast cancer patients followed over 24 years (Levi et al, 2003). The Breast Cancer Linkage Consortium studied cancer risks in BRCA mutation carriers and found that BRCA2 mutation carriers have an increased risk of developing malignant melanoma (2.58 relative risk) (The Breast Cancer Linkage Consortium, 1999), while BRCA1 mutation carriers have an increased risk for colon cancer and prostate cancer, but no significant excesses in rates of cancers of other body sites (Ford et al, 1994).…”
Section: Other Personal Medical Historymentioning
confidence: 99%